Environmental risk factors for congenital heart disease - Kalisch-Smith, J; Ved, N; Sparrow, D (Cold Spring Harbor Laboratory Press, 2019)
Congenital heart disease (CHD) has many forms and a wide range of causes. Clinically, it is important to understand the causes. This allows estimation of recurrence rate, guides treatment options, and may also be used to formulate public health advice to reduce the population prevalence of CHD. The recent advent of sophisticated genetic and genomic methods has led to the identification of more than 100 genes associated with CHD. However, despite these great strides, to date only one-third of CHD cases have been shown to have a simple genetic cause. This is because CHD can also be caused by oligogenic factors, environmental factors, and/or gene–environment interaction. Although solid evidence for environmental causes of CHD have been available for almost 80 years, it is only very recently that the molecular mechanisms for these risk factors have begun to be investigated. In this review, we describe the most important environmental CHD risk factors, and what is known about how they cause CHD.